2017
DOI: 10.12688/f1000research.12448.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trichoderma spp., Pseudomonas fluorescence and Bacillus subtilis for biological control of Ralstonia wilt of tomato

Abstract: Abstractis the major bacterial disease in tomato, Background: Ralstonia solanacearum which invades the roots of diverse plant hosts and colonizes xylem vessels causing wilt, especially in tropical, subtropical and warm-temperate regions. R.produces several toxins helping it to invade the plant's natural solanacearum defense mechanism. Native isolates of Trichoderma spp., Pseudomonas and can be used as biocontrol agents to control fluorescence Bacillus subtilis the bacterial wilt and combined application of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
(8 reference statements)
5
7
0
2
Order By: Relevance
“…The results could be attributed to the synergistic effect between the combinations of the two microorganisms in this treatment. These results were in harmony with those reported by Yendyo and Pandey (2017) that Trichoderma spp. and P. fluorescence seem to be more effective than treatment using each individual biocontrol agent that has been achieved 97% of (Morsy et al, 2009).…”
Section: Effects Of Isolates On Disease Incidence and Biocontrol Efficacysupporting
confidence: 92%
See 3 more Smart Citations
“…The results could be attributed to the synergistic effect between the combinations of the two microorganisms in this treatment. These results were in harmony with those reported by Yendyo and Pandey (2017) that Trichoderma spp. and P. fluorescence seem to be more effective than treatment using each individual biocontrol agent that has been achieved 97% of (Morsy et al, 2009).…”
Section: Effects Of Isolates On Disease Incidence and Biocontrol Efficacysupporting
confidence: 92%
“…AA2 and Pseudomonas fluorescens PFS were most potent inhibiting the growth of Ralstonia species and the field study indicated Trichoderma spp. and P, fluorescens alone were able to prevent 92 and 96% of the infection and combination of both were more effective, preventing 97% of infection compared to chemical control methods that prevented 94% of infection (Yendyo and Pandey, 2017). This shows the promising potential of native isolates of Trichoderma spp.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Además, se determinó la interacción directa de los antagonistas con el patógeno y la reducción de una enfermedad en progreso, ya que, las plántulas fueron infectadas antes de la inoculación con los antagonistas (Rajeswari y Kapoor, 2018). Esto determina una efectiva colonización de los antagonistas y permite reducir la variabilidad del control de la enfermedad en el campo (Yendyo et al, 2017). Se determinó la capacidad de los consorcios como potentes promotores de crecimiento, debido al incremento significativo en los valores observados.…”
Section: Resultados Y Discusiónunclassified